Analisis Faktor yang Berhubungan dengan Efikasi Diri Menyusui - Dina Mariana; Idayati Idayati (Jurnal Bidan Cerdas, 2022)
Introduction: Breastfeeding is a way of giving breast milk to babies that is effective in improving the quality of a child's health. Mother's belief in breastfeeding is a condition related to a psychological condition known as breastfeeding self-efficacy. Purpose: to analyze the factors related to breastfeeding self-efficacy in mothers at the Beru-beru Health Center, Mamuju Regency. Method: The type of research used is an observational study with a cross-sectional study design. The total sample of 81 people used a purposive sampling technique and data analysis used the Chi Square Test. The study was conducted in August – October 2022. Results: The results showed that observation of other people (p=0.049) and verbal persuasion (p=0.016) had a significant relationship with breastfeeding self-efficacy while for breastfeeding experience (p=0.182), physical and emotional condition (p=0.072) had no significant relationship with breastfeeding self-efficacy. Conclusion: The results of this study can be used in designing interventions to increase the self-efficacy of mothers in giving exclusive breastfeeding to their babies, so that it is hoped that it can provide support for government policies in order to increase the coverage of exclusive breastfeeding.